SCHOOL MEDIATION AS A SOCIAL TECHNOLOGY TO FIGHT VIOLENCE AND GUARANTEE RIGHTS TO THE LGBTQIA+ POPULATION (Revista Inclusiones, 2022)
The present study sought to reflect on the potential of conflict mediation to combatviolence and guarantee rights for the LGBTQIA+ population in the schoolenvironment. To this end, an extensive bibliographic research was carried out,encompassing scientific production, normative analysis and documentconsultations, in order to update existing data and carry out a theoreticalinvestigation in order to answer previous questions and those generated during thestudy. Mediation is a social technology that offers schools and individuals new formsof relationship that strengthen, day by day, a climate of healthy coexistence, bypreventing conflict, indiscipline and violence. However, conflicts arising fromdiscrimination and violence based on sexual orientation, gender identity orexpression demand a different treatment by the mediator, under penalty ofineffective conflict resolution obtained through school mediation.